Al / Al2O3 composite material with multilevel structure and preparation method thereof
By designing Al/Al2O3 composite materials with multi-stage structures, using frozen casting and pressure impregnation technology, the problem of difficulty in preparing high-precision complex multi-stage structure metal-ceramic composite materials is solved, and the high strength and toughness and low stress of the material are achieved Concentrated effect.
Patent Information
- Application Number
- CN202411640144.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional preparation methods are difficult to produce metal-ceramic composite materials with high-precision, complex multi-stage structures, resulting in stress concentrations in the material when it is carried, weakening the energy absorption advantage of the metal phase.
Al/Al2O3 composite materials designed with multi-level structures include primary structures (micro-nano-scale ceramic particles and Al metal layers), secondary structures (layered structures of micro-scale Al layer and ceramic-rich sheet layers) and tertiary structures (mm-scale continuous Al phase and ceramic rich columns) were prepared by frozen casting and pressure impregnation technology.
The coordinated strengthening and toughening mechanism of materials on different scales is realized, the strength and toughness of composite materials are improved, and the problems of stress concentration and strain localization are reduced.
Smart Images

Figure CN119433324A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to an Al / Al2O3 composite material with a multi-level structure and a preparation method thereof. Background Art
[0002] After a long period of natural selection and evolution, the hierarchical structure design commonly used by organisms has shown obvious advantages. For example, the sophisticated and complex hierarchical composite structure formed by pearl oysters at multiple length scales enables the material to produce synergistic strengthening and toughening mechanisms at different scales, making it show a mechanical response far beyond the conventional mixing law. This also brings important inspiration to artificial composite materials.
[0003] For metal-ceramic composites with broad application prospects, the optimal combination of strength and toughness can be obtained by giving full play to the contributions of the soft and hard phases. However, it is difficult for the current traditional manufacturing process to directly produce high-precision metal-ceramic composites with complex multi-level structures in a low-cost manner. Common methods such as metal infiltration usually prepare a ceramic skeleton first, and then infiltrate the ceramic body with molten metal. The ceramic phase inside the prefabricated ceramic skeleton prepared by traditional methods such as adding pore-forming agents, foaming or freeze casting is continuous, and its microstructure is monotonous and single in scale. In addition, the metal in the corresponding composite material is discontinuous or incompletely continuous, which makes the composite material prone to stress concentration when loaded, thereby weakening the energy absorption advantage of the metal phase; while other preparation methods, such as powder metallurgy, in-situ solidification, etc., are difficult to effectively regulate the matrix grain structure and the distribution of the reinforcement phase. The resulting composite microstructure is single, and affected by the interface energy, the reinforcement phase usually shifts and segregates to the grain boundary, and it is difficult to be evenly distributed in the composite material, and stress concentration is prone to occur when loaded. Summary of the invention
[0004] The purpose of the embodiments of the present invention is to provide an Al / Al2O3 composite material with a multi-level structure, aiming to solve the problems raised in the above background technology.
[0005] The embodiment of the present invention is implemented as follows: an Al / Al2O3 composite material with a multi-level structure, the composite material comprising: A primary structure, wherein the primary structure is composed of micro-nano-scale ceramic particles, and a micro-nano-scale Al metal layer is filled between the ceramic particles; A secondary structure, wherein the secondary structure is composed of a micron-sized Al layer and a ceramic-rich layer, wherein the micron-sized Al layer and the ceramic-rich layer are alternately arranged in a layered structure, and the ceramic-rich layer has a primary structure inside; The tertiary structure is composed of a millimeter or sub-millimeter scale continuous Al phase and isolated or continuous ceramic-rich columns, wherein the ceramic-rich columns have a secondary structure inside.
[0006] Preferably, the volume fraction of ceramic in the composite material is 10-40 vol.%; The volume fraction of ceramic in the ceramic-rich column is 30-60 vol.%, and the cross-sectional structure of the ceramic-rich column is one or more of a triangle, a rectangle, a honeycomb, a concave honeycomb, a circle, a broken line, and a wave.
[0007] Another object of the embodiment of the present invention is to provide a method for preparing an Al / Al2O3 composite material with a multi-level structure, comprising the following steps: (1) preparing a photocurable resin composed of a resin monomer, a diluent and a photoinitiator; wherein, by volume percentage, the resin monomer is 50-65%, the diluent is 35-50%, and the sum of the volume percentages of the resin monomer and the diluent is 100%; and a photoinitiator is additionally added, the amount of which, by mass percentage, accounts for 1-4% of the total mass of the resin monomer and the diluent; (2) ball-milling and mixing calcium carbonate powder, photocurable resin and dispersant into a prefabricated slurry; wherein, by volume percentage, the calcium carbonate powder is 20-40%, the photocurable resin is 60-80%, and the sum of the volume percentages of the calcium carbonate powder and the photocurable resin is 100%; additionally adding a dispersant, the amount of which, by mass percentage, is 0.5-1.5% of the calcium carbonate powder; (3) Designing a calcium carbonate resin model using modeling software, and making holes on the upper and lower surfaces to reserve the connection parts of the ceramics, using digital light processing technology to solidify the prefabricated slurry in step (2) to obtain a calcium carbonate resin model, and then using an organic solvent to clean the calcium carbonate resin model to remove excess slurry; (4) preparing a freezing slurry formed by ball-milling a ceramic powder, a solvent, a dispersant and a sintering aid; wherein, by volume percentage, the ceramic powder is 15-40%, the solvent is 60-85%, and the sum of the volume percentages of the ceramic powder and the solvent is 100%; the amount of the additional dispersant added is 0.2-1.5% of the ceramic powder by mass percentage, and the amount of the sintering aid added is 1-5% of the ceramic powder by mass percentage; (5) placing the calcium carbonate resin mold into a matching freezing mold, pouring the freezing slurry from step (4), and placing the freezing mold into a metal can, followed by vacuuming and pressurizing operations; (6) Using freeze casting technology, placing a freeze mold containing the freeze slurry and the calcium carbonate resin mold on a freezing platform to obtain a solidified ceramic body, and then freeze drying in a vacuum environment to remove the solidified solvent in the ceramic body; (7) Degreasing the ceramic body to remove organic matter, sintering it once, soaking it in a hydrochloric acid solution to remove residual calcium oxide after sintering, and finally sintering it twice to obtain a ceramic skeleton; (8) Liquid metal Al or Al alloy is injected into the ceramic skeleton using pressure infiltration technology to obtain an Al / Al2O3 composite material with a multi-level structure.
[0008] Preferably, in step (1), the resin monomer is an acrylic ester monomer; The diluent is one or more of camphene, tert-butyl alcohol, camphor, ethanol, polyethylene glycol 200 and polyethylene glycol 600; The photoinitiator is one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, a mixture of benzoyl formate, 2-isopropylthioxanthone and dibenzoyl; The mixing process is specifically heating magnetic stirring, with a rotation speed of 500-1000 rpm, a heating temperature of 25-50° C., and a stirring time of 20-60 min.
[0009] Preferably, in step (2), the dispersant is one or more of BYK 111, BYK 2001 and C-0043.
[0010] Preferably, in step (3), the structure of the calcium carbonate resin model designed using modeling software is one of rectangular, wavy, petal-shaped, circular, honeycomb, and triangular; The parameters of the digital light processing process are set as follows: layer thickness 20-80 μm, first layer exposure intensity 19-44 mW / cm 2 , first layer exposure time 2-8 s, normal layer exposure intensity 5-25 mW / cm 2 , normal layer exposure time is 0.5-4 s, and the number of first layers is 2-8 layers.
[0011] Preferably, in step (4), the solvent is one of water, camphene and tert-butanol; The particle size of the ceramic powder is 50 nm-10 μm; The dispersant is one or more of Dolapix Ce 64, PMAA-NH4, PMAA-Na, and PVA; The sintering aid is one or more of silica sol, TiO2, CuO, and MgO; The ball milling mixing process is specifically as follows: the ball milling speed is 100-300 rpm, the ball-to-material ratio is 1.5-5:1, and the ball milling time is 5-15 h.
[0012] Preferably, in step (5), the vacuuming and pressurizing operations are as follows: vacuuming to 10-100 Pa and maintaining for 15 min, and then introducing air to 0.1-0.6 MPa and maintaining for 5-10 min.
[0013] Preferably, in step (7), the degreasing process is specifically to increase the temperature to 450-600°C at a heating rate of 0.1-2°C / min, wherein the heating rate from 350°C to 450°C is 0.1-0.5°C / min; The primary sintering process is specifically to heat up to 1000-1200°C at a heating rate of 0.2-2°C / min, wherein the heating rate from 650°C to 750°C is 0.2-0.5°C / min; The soaking process in the hydrochloric acid solution is specifically as follows: the concentration of the hydrochloric acid solution used for soaking is 1-5 mol / L, soaking for more than 24 hours, and then putting it into deionized water and washing it in an ultrasonic cleaning machine for multiple times, each time for 5-10 minutes; The secondary sintering process is specifically to heat to 1150-1550°C at a heating rate of 5-10°C / min, keep the temperature for 60-120 min, and then cool to room temperature at a cooling rate of 2-10°C / min.
[0014] Preferably, in step (8), the process of injecting liquid metal Al or Al alloy into the ceramic skeleton by pressure infiltration technology is specifically as follows: placing a metal block on the ceramic skeleton, placing the metal block together in an alumina crucible, and placing the alumina crucible in an infiltration furnace, wherein the metal is pure Al or one of the Al alloys; After the infiltration furnace is evacuated to 1-10 Pa, it is heated to 700-850 °C at a heating rate of 5-10 °C / min, kept at this temperature for 5-10 min, and then high-purity argon is introduced into the vacuum furnace to 2-3 MPa; After the heat preservation and pressure holding are completed, cooling begins, cooling to the metal solidification point at a cooling rate of 5-10 ℃ / min, and then cooling to room temperature at 5 ℃ / min.
[0015] An Al / Al2O3 composite material with a multi-level structure provided in an embodiment of the present invention has a significant hierarchical composite structure at the millimeter, micrometer, and micro-nanometer scales, which solves the problem of single internal microstructure and scale of the composite material under traditional preparation methods; the metal phase of the composite material has a continuous hierarchical structure at the millimeter, micrometer, and micro-nanometer scales, and the reasonable size design realizes the combination of hard phase load-bearing and soft phase energy absorption, so that the material produces a synergistic strengthening and toughening mechanism at different scales, and has high toughness; at the same time, the composite material has a discontinuous ceramic-rich column structure inside, which solves the technical difficulty of traditional methods that are difficult to achieve isolated ceramic phase preparation, and effectively improves the problems of stress concentration and strain localization of metal-ceramic composite materials when bearing. The preparation process provided by the embodiment of the present invention has the advantages of flexible structural design, precise shape and size control, and low preparation cost; in addition, a wide range of selectable ceramic and metal materials are available, and the process has universal applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 A flow chart of a method for preparing an Al / Al2O3 composite material with a multi-level structure provided in an embodiment of the present invention; Figure 2 Macroscopic photos of calcium carbonate resin molds provided in Examples 1-3 of the present invention (a is a regular hexagonal honeycomb calcium carbonate resin mold of Example 1, b is a circular honeycomb calcium carbonate resin mold of Example 2, and c is an interpenetrating structure calcium carbonate resin mold of Example 3); Figure 3 Macroscopic photographs of the ceramic skeletons provided in Examples 1-3 of the present invention (a is the regular hexagonal honeycomb Al2O3 ceramic skeleton of Example 1, b is the circular Al2O3 ceramic skeleton of Example 2, and c is the interpenetrating Al2O3 ceramic skeleton of Example 3); Figure 4 a is the bending stress-strain curve of the regular hexagonal honeycomb Al / Al2O3 composite material at different maximum sintering temperatures (1150-1550 ℃) provided in the embodiments of the present invention, Figure 4 b is the bending stress-displacement curve of the single-side notched specimen of regular hexagonal honeycomb Al / Al2O3 composite material at different maximum sintering temperatures (1150-1550 ℃); Figure 5 The cross-sectional and longitudinal cross-sectional morphology results of the regular hexagonal honeycomb Al / Al2O3 composite material provided in Example 1 of the present invention (a is a macroscopic photo of the cross section, bd are microscopic photos; e is a macroscopic photo of the longitudinal section, fh are microscopic photos); Figure 6The fracture morphology results of the regular hexagonal honeycomb Al / Al2O3 composite material after three-point bending fracture provided in Example 1 of the present invention (ad is the microscopic morphology at different magnifications). DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0018] An Al / Al2O3 composite material with a multi-level structure, wherein the composite material completely retains the ceramic skeleton morphology, has a hierarchical structure at multiple scales of millimeter, micrometer and micro-nano, and the overall ceramic volume fraction of the composite material is 10-40 vol.%; The primary structure is micro-nano ceramic particles and micro-nano pure Al metal layers or Al alloy metal layers filled between the ceramic particles. The ceramic material is alumina, and the powder particle diameter of the ceramic material is 50 nm-10 μm. The secondary structure is a layered structure of Al-rich layers and ceramic-rich layers overlapping each other on a micrometer scale, with a layer thickness of 15-50 μm. The ceramic-rich layers have a primary structure at the microscopic level. The tertiary structure is a continuous Al phase and isolated (or continuous) ceramic-rich pillars on a millimeter and sub-millimeter scale, wherein the side length of the ceramic-rich pillars is 200 μm-2 mm, the spacing between the ceramic-rich pillars is 100 μm-2 mm, the ceramic-rich pillars have a secondary structure at the microscopic level, the ceramic volume fraction in the ceramic-rich pillars is 30-60 vol.%, and the cross-sectional structure of the ceramic-rich pillars includes but is not limited to triangle, rectangle, honeycomb, concave honeycomb, circle, broken line, and wave; The preparation process of the Al / Al2O3 composite material with a multi-level structure is as follows: Figure 1 As shown, the specific steps are as follows: (1) using magnetic stirring to mix the resin monomer, diluent and photoinitiator to prepare a photocurable resin, the rotation speed is 500-1000 rpm, the heating temperature is 25-50 ° C, and the stirring time is 20-60 min; Wherein, by volume percentage, 50-65% of the resin monomer, 35-50% of the diluent, the sum of the volume percentages of the resin monomer and the diluent is 100%; additionally, a photoinitiator is added, and the amount added by mass percentage accounts for 1-4% of the total mass of the resin monomer and the diluent; The resin monomer is an acrylate monomer; the diluent is one or more of camphene, tert-butyl alcohol, camphor, ethanol, polyethylene glycol 200 and polyethylene glycol 600; the photoinitiator is one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (PI-TPO), 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone (PI-907), a mixture of benzoyl formate, 2-isopropylthioxanthone (PI-ITX), and dibenzoyl; (2) ball-milling the calcium carbonate powder, the light-curing resin and the dispersant into a pre-made slurry, with a ball-milling speed of 300-1500 rpm, a ball-to-material ratio of 1.5-5:1, and a ball-milling time of 10-60 min; Wherein, by volume percentage, 20-40% calcium carbonate powder, 60-80% photocurable resin, the sum of the volume percentages of calcium carbonate powder and photocurable resin is 100%; additionally, a dispersant is added, and the amount added by mass percentage accounts for 0.5-1.5% of the calcium carbonate powder; The dispersant is one or more of BYK 111, BYK 2001 and C-0043; (3) Use modeling software to design a three-dimensional model diagram. The design structure includes but is not limited to rectangular, wavy, petal-shaped, circular, honeycomb, and triangular. The top and bottom of the model are opened with square or elliptical grooves or holes of a certain size to reserve channels for the slurry to flow into during the freeze casting process, thereby forming connections between the columns; use digital light processing technology to form a calcium carbonate resin mold. The process parameters used are: layer thickness 20-80 μm, first layer exposure intensity 19-44 mW / cm 2 , first layer exposure time 2-8 s; normal layer exposure intensity 5-25 mW / cm 2 , normal layer exposure time 0.5-4 s; first layer number 2-8 layers; internal printing structure of calcium carbonate resin model includes but is not limited to rectangle, wave, petal, circle, honeycomb, triangle; use organic solvent divalent ester (DBE) to clean it, the method is ultrasonic cleaning, the cleaning time is 5 min, the number of times is 2; (4) using a planetary ball mill to prepare a frozen slurry formed by ball milling a mixture of ceramic powder, solvent, dispersant and sintering aid, the ball milling speed is 100-300 rpm, the ball-to-material ratio is 0.5-1.5:1, and the ball milling time is 5-15 h; Among them, by volume percentage, 15-40% ceramic powder, 60-85% solvent, the sum of the volume percentages of ceramic powder and solvent is 100%; the amount of additional dispersant added by mass percentage accounts for 0.2-1.5% of the ceramic powder, and the amount of sintering aid added by mass percentage accounts for 1-15% of the ceramic powder; The solvent in the frozen slurry includes, but is not limited to, water, camphene, and tert-butyl alcohol (a non-acidic solvent that does not react with calcium carbonate); (5) Place the calcium carbonate resin mold into a freezing mold, pour in the freezing slurry and place in a metal sealed can, evacuate to 10-100 Pa and maintain for 15 min, then introduce air to 0.1-0.6 MPa and maintain for 5-10 min to remove bubbles in the slurry; (6) Using directional freezing technology, the calcium carbonate resin mold containing the slurry and the matching freezing mold are placed on a freezing platform for directional freezing. After solidification, the ceramic body is obtained, which is placed in a freeze dryer and freeze-dried in a vacuum environment (below 50 Pa) at -50 °C for more than 20 h to remove the solidified solvent in the ceramic body; (7) The frozen green body is degreased to remove organic matter, and then sintered once to obtain a certain strength. It is then soaked in a hydrochloric acid solution to remove residual calcium oxide after sintering, and then the soaked and cleaned sample is subjected to a secondary sintering; the degreasing process is: heating to 450-600 °C at 0.1-2 °C / min, of which the heating rate from 350 °C to 450 °C is 0.1-0.5 °C / min; the primary sintering process is: heating to 1000-1200 °C at 0.2-2 °C / min, of which the heating rate from 650 °C to 750 °C is 0.2-0.5 °C / min; the hydrochloric acid concentration used for soaking is 1-5 mol / L, and the soaking time is more than 24 hours. After soaking, the sample is placed in deionized water and washed twice in an ultrasonic cleaner, each time for 5-10 min; the secondary sintering process after removing CaO is: heating to 1150-1550 °C at 5-10 °C / min ℃, keep warm for 60-120 min, then cool to room temperature at 2-10 ℃ / min to obtain a ceramic skeleton; (8) Using pressure infiltration technology, place the metal Al block on top of the ceramic skeleton and put them into an alumina crucible, which is then placed in an infiltration furnace. After the infiltration furnace is evacuated to 5 Pa, heat it to 700-850 °C at 5-10 °C / min and keep it warm for 5-10 min. Then, introduce high-purity argon gas into the vacuum furnace to 2-3 MPa. After the insulation and pressure maintenance are completed, start cooling. The cooling method is: cool to the metal solidification point at 5-10 °C / min, and then cool to room temperature at 5 °C / min.
[0019] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0020] Example 1: An Al / Al2O3 composite material with a multi-level structure, the preparation steps of which are as follows: (1) Using magnetic stirring, resin monomer (30 vol.% 1,6-hexanediol diacrylate, 25 vol.% trimethylolpropane triacrylate), diluent (45 vol.% ethanol) and photoinitiator (2,4,6-trimethylbenzoyl-diphenylphosphine oxide, accounting for 4% of the mass of resin monomer and diluent) were mixed to prepare a light-curable resin. The rotation speed was 800 rpm, the heating temperature was 40 °C, and the stirring time was 30 min. (2) Calcium carbonate powder (D 50 =7.5 μm), photocurable resin (70 vol.%) and dispersant (BYK111, accounting for 1 wt.% of the mass of calcium carbonate powder) were mixed by ball milling to prepare a ceramic slurry with a solid content of 30 vol.%, the ball milling speed was 1200 rpm, the ball-to-material ratio was 2:1, and the ball milling time was 15 min; (3) A honeycomb 3D model was designed using modeling software. The honeycomb side length was 1 mm, the spacing was 200 μm, and the total height of the printed model was 25 mm. A square groove with a height of 2 mm and a width of 0.6 mm was opened at the bottom. An elliptical hole with a distance of 2.5 mm from the edge as the center was opened at the top. The long axis was 2 mm and the short axis was 0.6 mm. This was to reserve a channel for the slurry to flow into during the freeze casting process, thereby forming a connection between the columns and the columns. The model was saved as an STL file. The model was molded into a calcium carbonate resin mold using digital light processing technology. The process parameters used were: layer thickness 50 μm, first layer exposure intensity 40 mW / cm 2 , first layer exposure time 4 s, normal layer exposure intensity 20 mW / cm 2 , the exposure time of the normal layer is 1 s, and the number of the first layer is 3; it is cleaned with an organic solvent divalent ester by ultrasonic cleaning, the cleaning time is 5 min, and the number of times is 2; (4) A planetary ball mill was used to prepare a frozen slurry by mixing alumina Al2O3 (30 vol.%), water (70 vol.%), a dispersant (PVA accounting for 0.4 wt.% of the ceramic powder, Dolapix Ce 64 accounting for 1 wt.% of the ceramic powder), and silica sol accounting for 10 wt.% of the ceramic powder (SiO2 with a particle size of 30 nm as the active ingredient accounting for 30 wt.% of the silica sol) to prepare a frozen slurry. The rotation speed was 100 rpm and the ball milling time was 12 h. (5) Pour the frozen slurry into the calcium carbonate resin model, then press the calcium carbonate resin model into the frozen slurry and put it into a metal can. Then, evacuate to 50 Pa and keep it for 15 min. Finally, introduce air to 0.5 MPa and keep it for 5-10 min. (6) Place the mold filled with the frozen slurry on the freezing platform and set the freezing temperature to -40 °C. After freezing, use a hydraulic press to remove the mold, then place it in a freeze drying box, start the refrigeration program and turn on the vacuum pump for freeze drying; (7) The frozen green body is degreased to remove organic matter, and then sintered once to obtain a certain strength, and then soaked in a hydrochloric acid solution to remove residual calcium oxide after sintering; the degreasing process is: heating to 600 °C at 0.1-2 °C / min, of which the heating rate from 350 °C to 450 °C is 0.1 °C / min; the primary sintering process is: heating to 1150 °C at 0.2-2 °C / min, of which the heating rate from 650 °C to 750 °C is 0.2 °C / min; the hydrochloric acid concentration used for soaking is 2 mol / L, and the soaking time is more than 24 hours. After soaking, the sample is placed in deionized water and cleaned in an ultrasonic cleaner twice, each time for 5-10 min; (8) The demolded ceramic green body is subjected to secondary sintering by heating to 1350°C at 5°C / min, keeping the temperature for 120 min, and then cooling to room temperature at 5°C / min to obtain a ceramic skeleton; (9) Using pressure infiltration technology, the metal Al block is placed on top of the ceramic skeleton and placed together in an alumina crucible, which is then placed in an infiltration furnace. After the infiltration furnace is evacuated to 5 Pa, it is heated to 800 °C at 5 °C / min and kept warm for 5 min. Then, high-purity argon gas is introduced into the vacuum furnace to 2 MPa. After the insulation and pressure are completed, cooling begins. The cooling method is: cooling to the metal solidification point at 10 °C / min, and then cooling to room temperature at 5 °C / min to obtain a regular hexagonal honeycomb Al / Al2O3 composite material.
[0021] Example 2: An Al / Al2O3 composite material with a multi-level structure, the preparation steps of which are as follows: (1) Using magnetic stirring, resin monomer (25 vol.% trimethylolpropane triacrylate, 35 vol.% 1,6-hexanediol diacrylate), diluent (40 vol.% polyethylene glycol 200) and photoinitiator (PI-907, accounting for 4% of the mass of resin monomer and diluent) were mixed to prepare a light-curing resin. The rotation speed was 800 rpm, the heating temperature was 50 °C, and the stirring time was 20 min. Calcium carbonate powder (D 50 =7.5 μm), photocurable resin (65 vol.%) and dispersant (BYK111, accounting for 1 wt.% of the mass of calcium carbonate powder) were mixed by ball milling to prepare a ceramic slurry with a solid content of 35 vol.%, the ball milling speed was 1200 rpm, the ball-to-material ratio was 2:1, and the ball milling time was 20 min; (2) The cylindrical 3D model was designed using modeling software. The cylinder diameter was 1.8 mm, the center spacing was 2 mm, and the total height of the printed model was 30 mm. A square groove with a height of 2.2 mm and a width of 0.5 mm was opened at the bottom. An elliptical hole with a distance of 3 mm from the edge as the center was opened at the top. The long axis was 2.2 mm and the short axis was 0.5 mm. This was to reserve a channel for the slurry to flow into during the freeze casting process, thereby forming a connection between the columns and saving it in STL format. The model was molded into a calcium carbonate resin mold using digital light processing technology. The process parameters used were: layer thickness 45 μm, first layer exposure intensity 35 mW / cm 2 , first layer exposure time 3.5s, normal layer exposure intensity 16 mW / cm 2 , the exposure time of the normal layer is 1 s, and the number of the first layer is 3; it is cleaned with an organic solvent divalent ester by ultrasonic cleaning, the cleaning time is 5 min, and the number of times is 2; (3) A planetary ball mill was used to prepare a frozen slurry by mixing alumina Al2O3 (30 vol.%), water (70 vol.%), a dispersant (PMAA accounting for 1 wt.% of the ceramic powder, PVA accounting for 0.5 wt.% of the ceramic powder) and TiO2 accounting for 3 wt.% of the ceramic powder. The rotation speed was 110 rpm and the ball milling time was 12 h. The other parameters and steps are the same as those in Example 1, and an Al / Al2O3 composite material with continuous isolated Al2O3-rich phase cylindrical columns of metallic Al is obtained.
[0022] Example 3: An Al / Al2O3 composite material with a multi-level structure, the preparation steps of which are as follows: (1) Using magnetic stirring, resin monomer (25 vol.% 1,6-hexanediol diacrylate, 35 vol.% trimethylolpropane triacrylate), diluent (40 vol.% camphor) and photoinitiator (2,4,6-trimethylbenzoyl-diphenylphosphine oxide, accounting for 4% of the mass of resin monomer and diluent) were mixed to prepare a light-curing resin. The rotation speed was 800 rpm, the heating temperature was 60 °C, and the stirring time was 15 min. Calcium carbonate powder (D 50 =7.5 μm), photocurable resin (65 vol.%) and dispersant (BYK111, accounting for 1 wt.% of the mass of ceramic powder) were mixed by ball milling to prepare a ceramic slurry with a solid content of 30 vol.%, the ball milling speed was 1200 rpm, the ball-to-material ratio was 2:1, and the ball milling time was 10 min; (2) Use modeling software to design the interpenetrating structure 3D model. The total height of the printed model is 25 mm. Use the "Structure" function to create an interpenetrating structure model with a porosity of 80% and a structural unit size of 2 mm. Save it as an STL file. Use digital light processing technology to form a calcium carbonate resin mold. The process parameters used are: layer thickness 45 μm, first layer exposure intensity 42 mW / cm 2 , first layer exposure time 4 s, normal layer exposure intensity 20 mW / cm 2 , the exposure time of the normal layer is 2.5 s, and the number of the first layer is 3; it is cleaned with an organic solvent divalent ester by ultrasonic cleaning, the cleaning time is 5 min, and the number of times is 2; (3) A planetary ball mill was used to prepare a frozen slurry by mixing alumina Al2O3 (30 vol.%), water (70 vol.%), a dispersant (PMAA accounted for 1 wt.% of the ceramic powder, PVA accounted for 0.5 wt.% of the ceramic powder) and silica sol (SiO2 content accounted for 30 wt.% of the silica sol) to prepare a frozen slurry. The rotation speed was 120 rpm and the ball milling time was 10 h. Other parameters and steps were the same as those in Example 1, and an Al / Al2O3 composite material with a continuous metal Al and continuous Al2O3 ceramic interpenetrating structure was obtained.
[0023] Performance Test: The calcium carbonate resin films prepared in Examples 1-3 were analyzed and macroscopic photographs were obtained as follows: Figure 2 As shown; The ceramic skeletons prepared in Examples 1-3 were analyzed and macroscopic photos were obtained as follows: Figure 3 As shown; The maximum sintering temperature parameter in the preparation method of Example 1 was changed, and an orthogonal test was performed to analyze the regular hexagonal honeycomb Al / Al2O3 composite material at different maximum sintering temperatures (1150-1550 ℃), and the bending stress-strain curve and the bending stress-displacement curve of the single-side notch specimen were obtained. Figure 4 As shown, according to Figure 4 It can be seen that the sample with the highest sintering temperature of 1350 °C and Al2O3 content of 33.2 vol.% has a crack growth toughness K Jc 112 MPam 1 / 2 , crack initiation toughness K Ic 15 MPam 1 / 2 ; Its bending strength is 576 MPa, which is 7.38 times the strength of pure aluminum matrix; The cross-section and longitudinal section of the regular hexagonal honeycomb Al / Al2O3 composite material prepared in Example 1 were analyzed, and the results were as follows: Figure 5As shown, according to Figure 5 It can be seen that the composite material has a multi-level structure composed of Al2O3 ceramic phase and metal Al phase. The primary structure is micro-nano ceramic particles and micro-nano metal layers filled between ceramic particles (d, h); the secondary structure is a layered structure with metal-rich layers and ceramic-rich layers overlapping each other on the micron scale, with a layer thickness of about 20 microns (c, g); the tertiary structure is a regular hexagonal honeycomb continuous metal phase on the millimeter and submillimeter scale (layer thickness of about 160 microns) and isolated (or continuous) ceramic-rich columns (b, f); The fracture morphology of the regular hexagonal honeycomb Al / Al2O3 composite material prepared in Example 1 after three-point bending fracture was analyzed, and the results were as follows: Figure 6 As shown, the microscopic morphology under different magnifications can clearly show the hierarchical structure at multiple scales, where a shows a ceramic-rich column with a regular hexagonal honeycomb structure (tertiary structure); b shows a layered structure with alternating Al and Al2O3 (secondary structure); c and d show the micro-nanoscale Al2O3 particles in the ceramic-rich layer and the micro-nanoscale Al layer wrapped around the outside of the incompletely sintered Al2O3 particles (primary structure).
[0024] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An Al / Al2O3 composite material with a multi-level structure, characterized in that: The composite material comprises: A primary structure, wherein the primary structure is composed of micro-nano-scale ceramic particles, and a micro-nano-scale Al metal layer is filled between the ceramic particles; A secondary structure, wherein the secondary structure is composed of a micron-sized Al layer and a ceramic-rich layer, wherein the micron-sized Al layer and the ceramic-rich layer are alternately arranged in a layered structure, and the ceramic-rich layer has a primary structure inside; The tertiary structure is composed of a millimeter or sub-millimeter scale continuous Al phase and isolated or continuous ceramic-rich columns, wherein the ceramic-rich columns have a secondary structure inside.
2. The Al / Al2O3 composite material with a multi-level structure according to claim 1, characterized in that: The volume fraction of ceramic in the composite material is 10-40 vol.%; The volume fraction of ceramic in the ceramic-rich column is 30-60 vol.%, and the cross-sectional structure of the ceramic-rich column is one or more of a triangle, a rectangle, a honeycomb, a concave honeycomb, a circle, a broken line, and a wave.
3. A method for preparing the Al / Al2O3 composite material with a multi-level structure as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) preparing a photocurable resin composed of a resin monomer, a diluent and a photoinitiator; wherein, by volume percentage, the resin monomer is 50-65%, the diluent is 35-50%, and the sum of the volume percentages of the resin monomer and the diluent is 100%; and a photoinitiator is additionally added, the amount of which, by mass percentage, accounts for 1-4% of the total mass of the resin monomer and the diluent; (2) ball-milling and mixing calcium carbonate powder, photocurable resin and dispersant into a prefabricated slurry; wherein, by volume percentage, the calcium carbonate powder is 20-40%, the photocurable resin is 60-80%, and the sum of the volume percentages of the calcium carbonate powder and the photocurable resin is 100%; additionally adding a dispersant, the amount of which, by mass percentage, is 0.5-1.5% of the calcium carbonate powder; (3) Designing a calcium carbonate resin model using modeling software, and making holes on the upper and lower surfaces to reserve the connection parts of the ceramics, using digital light processing technology to solidify the prefabricated slurry in step (2) to obtain a calcium carbonate resin model, and then using an organic solvent to clean the calcium carbonate resin model to remove excess slurry; (4) preparing a freezing slurry formed by ball-milling a ceramic powder, a solvent, a dispersant and a sintering aid; wherein, by volume percentage, the ceramic powder is 15-40%, the solvent is 60-85%, and the sum of the volume percentages of the ceramic powder and the solvent is 100%; the amount of the additional dispersant added is 0.2-1.5% of the ceramic powder by mass percentage, and the amount of the sintering aid added is 1-5% of the ceramic powder by mass percentage; (5) placing the calcium carbonate resin mold into a matching freezing mold, pouring the freezing slurry from step (4), and placing the freezing mold into a metal can, followed by vacuuming and pressurizing operations; (6) Using freeze casting technology, placing a freeze mold containing the freeze slurry and the calcium carbonate resin mold on a freezing platform to obtain a solidified ceramic body, and then freeze drying in a vacuum environment to remove the solidified solvent in the ceramic body; (7) Degreasing the ceramic body to remove organic matter, sintering it once, soaking it in a hydrochloric acid solution to remove residual calcium oxide after sintering, and finally sintering it twice to obtain a ceramic skeleton; (8) Liquid metal Al or Al alloy is injected into the ceramic skeleton using pressure infiltration technology to obtain an Al / Al2O3 composite material with a multi-level structure.
4. The method for preparing the Al / Al2O3 composite material with a multi-level structure according to claim 3, characterized in that: In step (1), the resin monomer is an acrylic ester monomer; The diluent is one or more of camphene, tert-butyl alcohol, camphor, ethanol, polyethylene glycol 200 and polyethylene glycol 600; The photoinitiator is one or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, a mixture of benzoyl formate, 2-isopropylthioxanthone and dibenzoyl; The mixing process is specifically heating magnetic stirring, with a rotation speed of 500-1000 rpm, a heating temperature of 25-50° C., and a stirring time of 20-60 min.
5. The method for preparing the Al / Al2O3 composite material with a multi-level structure according to claim 3, characterized in that: In step (2), the dispersant is one or more of BYK 111, BYK 2001 and C-0043.
6. The method for preparing the Al / Al2O3 composite material with a multi-level structure according to claim 3, characterized in that: In step (3), the structure of the calcium carbonate resin model designed using modeling software is one of rectangular, wavy, petal-shaped, circular, honeycomb, and triangular; The parameters of the digital light processing process are set as follows: layer thickness 20-80 μm, first layer exposure intensity 19-44 mW / cm 2 , first layer exposure time 2-8 s, normal layer exposure intensity 5-25 mW / cm 2 , normal layer exposure time is 0.5-4 s, and the number of first layers is 2-8 layers.
7. The method for preparing the Al / Al2O3 composite material with a multi-level structure according to claim 3, characterized in that: In step (4), the solvent is one of water, camphene and tert-butyl alcohol; The particle size of the ceramic powder is 50 nm-10 μm; The dispersant is one or more of Dolapix Ce 64, PMAA-NH4, PMAA-Na, and PVA; The sintering aid is one or more of silica sol, TiO2, CuO, and MgO; The ball milling mixing process is specifically as follows: the ball milling speed is 100-300 rpm, the ball-to-material ratio is 1.5-5:1, and the ball milling time is 5-15 h.
8. The method for preparing the Al / Al2O3 composite material with a multi-level structure according to claim 3, characterized in that: In step (5), the vacuuming and pressurizing operation process is specifically to evacuate to 10-100 Pa and maintain for 15 min, then introduce air to 0.1-0.6 MPa and maintain for 5-10 min.
9. The method for preparing the Al / Al2O3 composite material with a multi-level structure according to claim 3, characterized in that: In step (7), the degreasing process is specifically to increase the temperature to 450-600°C at a heating rate of 0.1-2°C / min, wherein the heating rate from 350°C to 450°C is 0.1-0.5°C / min; The primary sintering process is specifically to heat up to 1000-1200°C at a heating rate of 0.2-2°C / min, wherein the heating rate from 650°C to 750°C is 0.2-0.5°C / min; The soaking process in the hydrochloric acid solution is specifically as follows: the concentration of the hydrochloric acid solution used for soaking is 1-5 mol / L, soaking for more than 24 hours, and then putting it into deionized water and washing it in an ultrasonic cleaning machine for multiple times, each time for 5-10 minutes; The secondary sintering process is specifically to heat to 1150-1550°C at a heating rate of 5-10°C / min, keep the temperature for 60-120 min, and then cool to room temperature at a cooling rate of 2-10°C / min.
10. The method for preparing the Al / Al2O3 composite material with a multi-level structure according to claim 3, characterized in that: In step (8), the process of injecting liquid metal Al or Al alloy into the ceramic skeleton by pressure infiltration technology is specifically as follows: placing a metal block on the ceramic skeleton, placing the metal block together in an alumina crucible, and placing the alumina crucible in an infiltration furnace, wherein the metal is pure Al or one of the Al alloys; After the infiltration furnace is evacuated to 1-10 Pa, it is heated to 700-850 °C at a heating rate of 5-10 °C / min, kept at this temperature for 5-10 minutes, and then high-purity argon gas is introduced into the vacuum furnace to 2-3 MPa; After the heat preservation and pressure holding are completed, cooling begins, cooling to the metal solidification point at a cooling rate of 5-10 ℃ / min, and then cooling to room temperature at 5 ℃ / min.
Citation Information
Cited By
A biomimetic composite material and a multi-stage assisted directional preparation method thereof
CN120400596B